2006
DOI: 10.7202/012842ar
|View full text |Cite
|
Sign up to set email alerts
|

Effets de la diffusion des technologies de l’information sur la croissance potentielle et observée

Abstract: Résumé L’étude propose une analyse des effets de l’émergence et de la diffusion des technologies de l’information sur la croissance potentielle et observée de l’output et de la productivité du travail en France, au cours des deux dernières décennies. De façon habituelle, les technologies de l’information regroupent ici le matériel informatique, les logiciels et les matériels de communication. Il en ressort que la diffusion des technologies de l’information élève… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In France, Cette et al (2005) found that ICTs diffusion has a positive effect on potential growth. Draca et al 2006conducted a broad review of both the microeconomic and macroeconomic literature on the effects of ICTs on productivity and concluded that the Solow paradox does not hold.…”
Section: Some Empirical Evidencesmentioning
confidence: 99%
See 1 more Smart Citation
“…In France, Cette et al (2005) found that ICTs diffusion has a positive effect on potential growth. Draca et al 2006conducted a broad review of both the microeconomic and macroeconomic literature on the effects of ICTs on productivity and concluded that the Solow paradox does not hold.…”
Section: Some Empirical Evidencesmentioning
confidence: 99%
“…In the present research it depends on the level of ICTs diffusion in the economy. This ICTs diffusion affects the level of total factor productivity in an economy (Cette et al, 2005;Johnson, 2016). Thus, endogenous technical progress is formalized as follows:…”
Section: Empirical Specification Of the Modelmentioning
confidence: 99%